The Renewal of Medieval Metaphysics Berthold of Moosburg's Expositio on Proclus' Elements of Theology - Calma, Dragos; King, Evan (History of Metaphysics: Ancient, 2021)
This is the first volume exclusively devoted to the Expositio by Berthold of Moosburg (c.1295-c.1361) on Proclus' Elements of Theology. The breadth of its vision surpasses every other known commentary on the Elements of Theology, for it seeks to present a coherent account of the Platonic tradition as such (unified through the concord of Proclus and Dionysius) and at the same time to consolidate and transform a legacy of metaphysics developed in the German-speaking lands by Peripatetic authors (like Albert the Great, Ulrich of Strassburg, and Dietrich of Freiberg). This volume aims to provide a basis for further research and discussion of this unduly overlooked commentary, whose historical-philosophical importance as an attempt to refound Western metaphysics is beginning to be recognized.. Readership: Scholars and students interested in the history of metaphysics, the Platonic tradition, and the intellectual milieu of the German Dominicans from Albert the Great to the mid-14th century.